2023
DOI: 10.1002/ehf2.14380
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, outcome, and therapeutic effect of tafamidis in wild‐type transthyretin amyloid cardiomyopathy

Abstract: Aims Tafamidis improves prognosis in patients with transthyretin amyloid cardiomyopathy (ATTR‐CM). However, real‐world data on the therapeutic effect of tafamidis are lacking. This study aimed to evaluate the clinical course, outcomes, and effectivity monitoring of the therapeutic effect of tafamidis in patients with ATTR‐CM. Methods and results This is a single‐centre, retrospective observational study. We evaluated the clinical characteristics and outcomes in 125 consecutive patients with wild‐type ATTR‐CM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…Ten conference abstracts, 8 articles 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 with overlapping data from the ATTR-ACT study, 6 and 4 studies 33 , 34 , 35 , 36 without available data for analysis were excluded. Finally, fifteen articles, 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 19 , 20 , 21 , 22 involving a total of 2765 patients, were included in the meta-analysis. The study and patient characteristics are summarized in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten conference abstracts, 8 articles 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 with overlapping data from the ATTR-ACT study, 6 and 4 studies 33 , 34 , 35 , 36 without available data for analysis were excluded. Finally, fifteen articles, 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 19 , 20 , 21 , 22 involving a total of 2765 patients, were included in the meta-analysis. The study and patient characteristics are summarized in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…678 (28.0%) patients died or received heart transplantation in nine studies. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 In addition, a total of 1060 patients with wild-type ATTR (wtATTR) in 4 articles 7 , 10 , 11 , 13 and 78 patients with hereditary ATTR (hATTR) in 1 article 12 were included for subgroup analysis. A flowchart of the study is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations